2008
DOI: 10.1111/j.1600-6143.2008.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

T cells in Cardiac Allograft Vasculopathy Are Skewed to Memory Th-1 Cells in the Presence of a Distinct Th-2 Population

Abstract: Cardiac allograft vasculopathy (CAV) in heart trans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
(59 reference statements)
4
21
0
Order By: Relevance
“…This study also showed a significant population of CD4+ T-cells expressing CCR3 and CCR8 (Th2 phenotype). The presence of this population in human TV may explain the proliferative response/matrix deposition/remodeling, which are also characteristic features of TV 12.…”
Section: Chemokine-cc Chemokine Receptormentioning
confidence: 97%
See 1 more Smart Citation
“…This study also showed a significant population of CD4+ T-cells expressing CCR3 and CCR8 (Th2 phenotype). The presence of this population in human TV may explain the proliferative response/matrix deposition/remodeling, which are also characteristic features of TV 12.…”
Section: Chemokine-cc Chemokine Receptormentioning
confidence: 97%
“…Additionally, the current immunosuppressive therapies are quite effective against acute rejection, but have failed to significantly alter the incidence and/or course of TV. There is also experimental and clinical evidence that the chemotactic mediators of mononuclear cell recruitment in acute rejection may be different from those in TV 5, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac allograft vasculopathy (CAV), a typical feature of chronic rejection, involves diffuse narrowing and occlusion of graft vessels. Several investigations have demonstrated that chronic rejection is associated with up-regulation of proinflammatory cytokines such as IL-17A and interferongamma (IFN-g) in allograft (3,4). In a model of CAV, graft recipients lacking the Th1 transcription factor T-bet have exacerbated vasculopathy associated with enhanced IL-17-producing CD4 þ cells infiltration (3).…”
Section: Introductionmentioning
confidence: 99%
“…In human coronary arteries, 5-to 10-fold fewer leukocytes are detected in the media than in the intima or adventitia of specimens with transplant vasculopathy, and no lymphocyte markers are detected in the media of control specimens. 92,93 The sparse medial infiltrates in arteriosclerotic arteries are generally associated with a preservation of VSMCs in that compartment, despite evidence of cellular injury elsewhere in the vessel wall. It is therefore not unexpected that VSMCs may remain functional even in the presence of endothelial dysfunction.…”
Section: Operational and Failed Medial Immunoprivilege In Arterial DImentioning
confidence: 99%